Hackable Instruments: Supporting Appropriation and Modification in Digital Musical Interaction - Zappi, Victor; McPherson, Andrew (Frontiers in ICT, 2018)
This paper investigates the appropriation of digital musical instruments, wherein the performer develops a personal working relationship with an instrument that may differ from the designer's intent. Two studies are presented which explore different facets of appropriation. First, a highly restrictive instrument was designed to assess the effects of constraint on unexpected creative use. Second, a digital instrument was created which initially shared several constraints and interaction modalities with the first instrument, but which could be rewired by the performer to discover sounds not directly anticipated by the designers. Each instrument was studied with 10 musicians working individually to prepare public performances on the instrument. The results suggest that constrained musical interactions can promote the discovery of unusual and idiosyncratic playing techniques, and that tighter constraints may paradoxically lead to a richer performer experience. The diversity of ways in which the rewirable instrument was modified and used indicates that its design is open to interpretation by the performer, who may discover interaction modalities that were not anticipated by the designers.